The Effects of Covid-19 on Development of Deep Venous Thrombosis: Bibliographic Review (Global Journal of Medical Research, 1970)
The new coronavirus 2019 (COVID-19) is clinically characterized by the multisystemic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), whose symptoms and prognosis depend on the stage of the disease in which the patient is. In aggravating cases, it is necessary to use mechanical ventilation or treatment in intensive care units (ICU), taking into account the high risk of mortality. Although the fundamental clinical features of the disease are respiratory, neurological, renal, digestive, cardiac and other organ complications also exist. The work in question, given the volume of clinical trials, seeks to effectively investigate potential therapies for COVID-19, highlighting the need to produce high-quality evidence. In addition, the biological plausibility of the thrombotic risk in SARS-CoV-2 and its cardiac involvement due to the exacerbated inflammatory response and due to pre-existing manifestations or due to acquired manifestations was discussed. Therefore, we carried out a systematic review of the literature, reporting measures to assess detectable changes in this scenario and their relationship with clinical severity.
Keywords: covid-19; sars-cov-2; deep vein thrombosis; coagulation